Growth characteristics, economics and hair mineral status of camel calves reared indifferent systems of management - BHAKAT, CHAMPAK; SAINI, NIRMALA; PATHAK, K ML (The Indian Journal of Animal Sciences, 2011)
Management systems were compared by conducting 2 trials with different feeding practices. Trials 1 and 2 were conducted by feeding guar phalgati and moth chara as manger feeding, respectively, for 165 days each to 5 camel calves each under intensive system of management (ISM) and semi-intensive system of management (SIM). Total gain in body weight was higher in SIM than ISM group in both the trials. Mean body weight and average growth rate significantly increased in SIM as compared to ISM group at the end of both the trials. The mean moth chara intake was significantly (P<0.05) more in ISM than SIM. The important hair minerals (calcium, magnesium, copper, zinc, iron and manganese) increased significantly in SIM as compared to ISM group. The manganese status varied significantly (P<0.05) between groups in moth chara trial. Feeding cost/calf/day and total cost were high in ISM than SIM group in both the trials. Total cost/kg body weight gain was quite less and economical in SIM as compared to ISM group. The study indicated SIM better than ISM for economic rearing of camel calf.